Synthesis, characterization and cytotoxicity evaluation of carboxylated carbon nanotubes functionalized with silibinin, betulinic acid and levodopa for drug delivery - Tan, Julia Meihua (2015)
Current methods of conventional drugs administered via liquids or tablets are often faced with problems like inefficient biodistribution, low solubility, poor bioavailability,long term toxicity and limited drug efficacy. As a result, many efforts have been carried out in the past to overcome the above mentioned limitations. This has led to the development of nanomaterial-based carrier as novel drug delivery system. In this study, commercially available carboxylated carbon nanotubes (CNTs) were used as the nano drug carrier due to their attractive physico-chemical properties which facilitate functionalization of therapeutic molecules onto their external walls or being encapsulated inside the nanotubes. Therefore, the main objective of the present work was to develop drug delivery formulation for silibinin (SB), betulinic acid (BA) and levodopa (LD) with carboxylated single walled (SWCNTs-COOH) and multiwalled carbon nanotubes (MWCNTs-COOH) separately for enhanced delivery efficiency into targeted cells with sustained-release effect. The resulting five nanohybrids, namely SWCNTs-SB, MWCNTs-SB, SWCNTs-BA,MWCNTs-BA and SWCNTs-LD, were prepared by non-covalent method via - and hydrogen bonds as well as hydrophobic interactions without the use of any cross-linker agent. The physico-chemical properties of the resulting nanohybrids, i.e. chemical interaction, elemental composition, crystallinity, thermal property, surface morphology,drug loading capacity and drug releasing characteristic were studied using Fourier transform infrared (FTIR) and Raman spectroscopies, elemental analysis (CHN-S),powder X-ray diffractometry (PXRD), thermogravimetric analysis (TGA), transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM) and ultraviolet-visibile spectrophotometry (UV-Vis). In order to assess the cytotoxicity characteristic of the synthesized nanohybrids, human cancer cell lines HepG2 (human liver hepatocellular carcinoma cell lines) and A549 (human lung adenocarcinoma epithelial cell lines) were used in comparison to normal cell lines MRC-5 (human lung cell lines), 3T3 (mouse fibroblast cell lines) and PC12 (rat neuronal cell lines). The loading of drug in SWCNTs-SB, MWCNTs-SB, SWCNTs-BA, MWCNTs-BA and SWCNTs-LD nanohybrids was estimated to be around 46.0, 35.1, 20.0, 14.8 and 38.2 w/w%, respectively as determined by UV-Vis, and these values have been verified by TGA. Both FTIR and Raman spectroscopy studies confirmed that the conjugation process has taken place between drugs and the nanocarriers. The PXRD results showed that tubular structures of the nanocarriers were not affected by drug loading mechanism. Drug release profiles have been investigated at different pH values, showing the influence of pH on the drug release process. In addition, the synthesized nanohybrids possessed favourable sustained-release property to be used in a controlledrelease formulation, with satisfactory coefficients conformed well to the pseudo-second order release kinetic model. Preliminary in vitro cytotoxicity studies suggest that the drug-loaded nanohybrids (i.e. SWCNTs-SB, MWCNTs-SB, SWCNTs-BA and MWCNTs-BA) are not acutely toxic while significantly inhibiting the growth of cancer cells in comparison with pure drugs after 72 hours of treatment using MTT [3-(4,5-dimethylthiazolyl-2)-2,5- diphenyltetrazolium bromide] assay. Cell viability assay was also performed in PC12 cell lines, a widely used in vitro Parkinson‘s model for neurotoxicity study, in order to investigate their potential effects on normal neuronal cells. It was found that the synthesized SWCNTs-LD did not compromise the cell viability of PC12 cells but remain stable throughout the experiment. With the addition of the surface coating agents, the initial burst of drugs was dramatically improved and thus, resulted in a more prolonged and sustained release fashion. In general, the coated nanohybrids exhibit a pseudo-second-order release kinetics which was driven by the ion exchange process between the ionized nanohybrids and the anions in the release medium. On top of that, it was noted that the surfactant and polymer coating improved the biocompatibility of the drug-loaded nanohybrids significantly in comparison to the uncoated ones. In conclusion, the findings from this work indicate that the carboxylated CNTs with the desired properties could be developed as an efficient drug nanocarrier to noncovalently conjugate poorly water-soluble drug for effective drug delivery in cancer chemotherapies and the treatment of neurodegenerative diseases.